Evaluation of Indonesian Food Politics and Fiscal Politics Support - Ika, Syahrir; Setiawan, Hadi; Damayanty, Sofia Arie (Jurnal Kajian Ekonomi dan Keuangan, 2015)
The Indonesian Constitution mandates the government to keep the food sovereignty in terms of availability, affordability, and the fulfillment of adequate food consumption with safety, quality, and nutritionally balanced. In food politics, the government has a number of policies and programs to achieve food self-sufficiency such as the provision of agricultural land, fertilizer, pesticides, seeds, irrigation, farmers' education, and financing supports. In terms of fiscal policy, the government annually allocates funds to support food self-sufficiency programs. Unfortunetaly, Indonesia still in the stage of below achieving a food self-sufficiency; the government still imports some strategic foodstuffs such as rice, corn, soybeans, sugar, and meat. Low production of foodstuffs bring about a decrease in agricultural sector contribution to GDP. This article aims to evaluate the effectiveness of government policy on food and fiscal policy support. Using secondary data, the study tries to describe using the approach of 'The Context, Links, and Evidence Framework". The study concludes that although the government has a strong commitment to have food sovereignty, but still difficult to achieve food selfsufficiency and food security. Therefore the authors recommend a policy package which includes nine priority programs to be considered by the government.